The anabolic catabolic transforming agent (ACTA) espindolol increases muscle mass and decreases fat mass in old rats. Issue 2 (22nd November 2013) - Pötsch, Mareike S.; Tschirner, Anika; Palus, Sandra; von Haehling, Stephan; Doehner, Wolfram; Beadle, John; Coats, Andrew J. S.; Anker, Stefan D.; Springer, Jochen
Abstract : Background: Sarcopenia, the age‐related, progressive loss of skeletal muscle mass, strength, and function, is a considerable socioeconomic burden by increasing risks of falls, fractures, and frailty. Moreover, sarcopenic patients are often obese and therapeutic options are very limited. Methods: Here, we assessed the efficacy of espindolol on muscle mass in 19‐month‐old male Wistar Han rats (weight, 555 ± 18 g), including safety issues. Rats were randomized to treatment with 3 mg/kg/day espindolol ( n  = 8) or placebo ( n  = 14) for 31 days. Results: Placebo‐treated rats progressively lost body weight (−15.5 ± 7.2 g), lean mass (−1.5 ± 4.2 g), and fat mass (−15.6 ± 2.7 g), while espindolol treatment increased body weight (+8.0 ± 6.1 g, p  < 0.05), particularly lean mass (+43.4 ± 3.5 g, p  < 0.001), and reduced fat mass further (−38.6 ± 3.4 g, p  < 0.001). Anabolic/catabolic signaling was assessed in gastrocnemius muscle. Espindolol decreased proteasome and caspase‐3 proteolytic activities by approximately 50 % (all p  < 0.05). Western blotting showed a reduced expression of key catabolic regulators, including NFκB, MuRF1, and LC‐3 (all p  < 0.01). The 50‐ and 26‐kDa forms of myostatin were downregulated fivefold and 20‐fold, respectively (both p  < 0.001). Moreover, 4E‐BP‐1 was reduced fivefold ( p  < 0.01), while phospho‐PI3K was upregulated fivefold ( p  < 0.001), although Akt expression and phosphorylation were lower compared to placebo (all p  < 0.05). No regulation of p38 and expression of ERK1/2 were observed, while phosphorylation of p38 was reduced (−54 %, p  < 0.001) and ERK1/2 was increased (115 and 83 %, respectively, both p  < 0.01). Espindolol did not affect cardiac function (echocardiography) or clinical plasma parameters. Conclusion: Espindolol reversed the effects of aging/sarcopenia, particularly loss of muscle mass and increased fat mass. Thus, espindolol is an attractive candidate drug for the treatment of sarcopenia patients. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐013‐0125‐7) contains supplementary material.